Editorial Comments - Marie Poggenpoel; Annatjie Botes (AOSIS, 2000)
We as health professionals are facing multiple challenges in our changing South African society. Some of these challenges and possible solutions are described by authors in different articles in this edition of Health SA Gesondheid. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.